ANALISIS PENGARUH LEVERAGE, PROFITABILITY, DAN FOREIGN OWNERSHIP TERHADAP PENGUNGKAPAN INFORMASI TANGGUNG JAWAB SOSIAL PERUSAHAAN (CORPORATE SOCIAL RESPONSIBILITY) - Handoyo, Sigit; Jakasurya, Tito (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2017)
Corporate Social Responsibility is defined as the voluntary activities undertaken by a company to operate in economic, social and environmentally sustainable manner. It's based on Pasal 74 Undang-Undang Perseroan Terbatas No. 40 Tahun 2007. The research aimed to analyze the factors influencing disclosure level of corporate social responsibility at mining sector that listed at Indonesian Stock Exchange (IDX) period 2013-2014. In this research caracteristics of the company are consisting of leverage, profitability, and foreign ownership. The population taken in this research was all companies at mining sector that listed in IDX from 2013 to 2014. The method of data analisys was linear regression analisys with SPSS 20. Multiple linear regression analysis technique that used in this research to determine the effect of leverage, profitability and foreign ownership to Corporate Social Responsibility disclosure. Index of corporate social responsibility (CSR) is measured with company's indicators disclosed by the number of indicator is set on G4 by Global Reporting Initiative (GRI). Leverage is defined by debt to asset ratio (DAR), profitability is defined by return on assets (ROA), and foreign ownership is defined by the amount of foreign ownership divided by number of outstanding shares . The result of this research showed that leverage and profitability have a positive and significant effect on the CSR disclosure, while the foreign ownership have no effect on CSR disclosure at the mining companies in Indonesia.
Keywords: Corporate Social Responsibility, Leverage, profitability, Foreign Ownership.